PENGARUH WORK-LIFE BALANCE DAN KOMPENSASI TERHADAP KEPUASAN KERJA TENAGA KESEHATAN PADA PUSKESMAS MEPANGA KECAMATAN MEPANGA KABUPATEN PARIGI MOUTONG - Arafah, Moh.; Novi Rianti, Ni Made (Jurnal Metaverse ADPERTISI, 2024)
The purpose of this research is to find out how much influence Work-Life Balance and Compensation have on employee job satisfaction, both simultaneously and partially. he data analysis method in this research uses multiple linear regression analysis. The results of this research show that Work-Life Balance and compensation simultaneously have a significant influence on Employee Job Satisfaction at the Mepanga Community Health Center, Mepanga District, Parigi Moutong Regency. Partially, Work-Life Balance obtained a significant value for the influence of X1 against Y is 0.807> 0.05 and the value of tcount 0.245 2,02269, so it can be concluded that H2 is accepted which means there is an influence X2 on the variable Y.